Mercury in liver and feathers of some birds of prey in Rio de Janeiro State, Brazil: Preliminary results (Research, Society and Development, 2024)
Birds of prey at higher trophic levels are particularly vulnerable to mercury pollution and can serve as indicators of trace elements in different ecosystems. Thus, the aim of this study was to evaluate the presence of mercury in feathers and livers in some birds of prey that occur in the State of Rio de Janeiro, Brazil. Eleven livers were collected from birds of pray during routine necropsies performed at the Rio de Janeiro Zoological Garden, and the feathers from animals in rehabilitation/release process. The results showed mercury concentrations ranged from 0.5 mg / kg to 1.3074 mg / kg in livers and from 0.3376 mg / kg to 3.000 mg / kg in feathers. Liver samples can be collected through invasive methods like biopsies, which involve anesthesia and handling of the bird, or during routine necropsies in zoological collections, breeding grounds, and from deceased birds found in the field, especially those affected by trampling or firearm injuries. Alternatively, analyzing feathers for mercury provides a practical, cost-effective, and non-invasive method that avoids risking harm to the bird's physical well-being.